Method of TOPSIS in Recipients of Home Improvement Assistance in South Siantar District at Pematangsiantar Tarukim Office - Fikri Yatussa'ada; Muhammad Zarlis; Sumarno Sumarno (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2019)
The construction of uninhabitable houses is a government program especially from the Social Service to provide housing development assistance for the poor. However, in its realization, funding assistance from the government is often still lacking and even not on target. Therefore this study aims to build a decision support system that has the ability to analyze in determining the community that is eligible to receive housing repairs. The SPK method used in this study is the TOPSIS method. This method uses the principle that the chosen alternative must have the shortest distance from the positive ideal solution and the farthest from the negative ideal solution from a geometric point of view by using the Euclidean distance to determine the relative proximity of an alternative to the optimal solution. Research data obtained from the Department of public housing and residential areas pematangsiantar city using interviews, observation and literature study methods needed to help solve problems. This study uses 10 alternatives and 7 criteria. After calculating the analysis, families who are entitled to help with house repairs are alternative 7 on behalf of the Piatur Siringgo-Ringgo.